(untitled) (Journal of Forensic Medicine & Toxicology, 2021)
Detection of pressure ulcers in a hospitalized patient could lead to a medical negligence litigation. But, mere occurrence of such ulcers should not be viewed as negligent care, unless there is evidence to prove that the care givers did nothing to prevent or heal them. mean poor care, as there may be aremany reasons for the development of the pressure ulcers of which several are beyond the control of the care givers.2 So, the complainants need to categorically show evidence of breach of duty by the hospitals and staff along with absence of record of the measures taken either to prevent or improve the healing of the pressure ulcers in the patient to make them liable for medical negligence.